Remittance in Nepal: Boon or Curse? - Satyal, Vikash Raj (Economic Journal of Nepal, 2014)
Remittance, in general, has been considered in Nepal a boon for economic uplift. However, there are also various negative dimensions of a remittance economy such as labour drain, unproductiveness of economy, etc. At the national level, foreign employment is only a temporary solution to unemployment and it should not be prolonged as it generates significant negative impacts on the overall national economy. This paper attempts to explore the relationship of remittance with some macro-economic variables using standard econometric analysis. Results from this analysis show that remittance deteriorates trade balance by increasing imports; it has, by and large, not improved the investment sector, and has increased inflation in the markeThe Economic Journal of Nepal, Vol. 34, No. 1, January - March 2011 (Issue N0. 133)Uploaded date: 3/27/2014